MODERN DIAGNOSIS AND TREATMENT OF LIVER ABSCESSES - Yakhshiboev S. S. (Journals Park Publishing, 2023)
Surgical method treatment of abdominal abscesses is the leading method. With open surgical interventions, mortality remains at the level of 18-24%, interventions under radiation hardware control can reduce mortality to 12-17% and generally improve the results of treatment of this category of patients. The purpose of our work is to improve the timely diagnosis and surgical treatment of liver abscess. Material and methods. The material for the study was obtained by retrospective analysis of the medical histories of patients who were in our medical institutions from 2015 to 2021. They comprised 75 patients. Patients are divided into two groups. Conclusion. The main group and the comparison group after treatment of the abscess cavity with antiseptics (chlorhexidine and Dekasan), the analysis of crops showed that after the end of the course of treatment, flushes from the residual cavities of bacterial growth were not given. This means the high bactericidal effectiveness of these antiseptics.
Keywords: liver abscess; complication; surgical method treatment; Dekasan solution.